FORMULASI LOTION EKSTRAK METHANOL DAUN KELOR (Moringa oleifera) DENGAN AKTIVITAS ANTIBAKTERI (Lotion Formulation of Moringa Leaves (Moringa Oleifera) Methanol Extract with Antibacterial Activity) - Stefani Santi Widhiastuti (Research Center for Biology-Indonesian Institute of Sciences, 2022)
ABSTRACTThe skin has an important function in the body's first line of defense. Lotion is used to maintain skin health, one of which is from microorganism infection by the presence of antibacterial substances in the formula. One of the plants that has antibacterial activity is Moringa (Moringa oleifera). The aim of this study was to make a lotion formula containing methanol extract of Moringa leaves which has antibacterial activity. The research was carried out from the extraction stage, phytochemical assay, lotion formulation, and antibacterial activity assay of the extract and lotion. Based on the results of phytochemical assay, methanol extract of Moringa leaves contains saponins, flavonoids, tannins, alkaloids and steroids, but does not contain triterpenoids. Moringa leaves extract has antibacterial activity against E. coli, S. aureus, and P. aeruginosa, where the activity increases along with increasing extract concentration. The lotion formula with 3% extract content is the optimum formula with the best antibacterial activity compared to other formulas, lotion base, and positive control with very strong antibacterial activity, seen from the inhibition zone diameter of more than 20 mm against E. coli, S. aureus, and P. aeruginosa. Keywords: kelor (Moringa oleifera), antibacterial activity, lotion ABSTRAK Kulit memiliki fungsi penting dalam pertahanan pertama tubuh. Lotion digunakan untuk menjaga kesehatan kulit salah satunya dari infeksi mikroorganisme dengan adanya kandungan zat antibakteri dalam sediaan. Salah satu tanaman yang memiliki aktivitas antibakteri adalah kelor (Moringa oleifera). Tujuan penelitian ini adalah membuat formula lotion dengan kandungan ekstrak methanol daun kelor yang memiliki aktivitas antibakteri. Penelitian dilakukan mulai dari tahap ekstraksi, uji kandungan fitokimia ekstrak, uji aktivitas antibakteri ekstrak, pembuatan formula lotion dan uji aktivitas antibakteri lotion. Berdasarkan hasil uji fitokimia, ekstrak methanol daun kelor mengandung saponin, flavonoid, tanin, alkaloid dan steroid, namun tidak mengandung triterpenoid. Ekstrak methanol daun kelor memiliki aktivitas antibakteri terhadap E. coli, S. aureus, dan P. aeruginosa, dimana aktivitasnya semakin meningkat seiring dengan meningkatnya konsentrasi ekstrak. Formula lootion dengan kandungan ekstrak sebesar 3% merupakan formula optimum dengan aktivitas antibakteri paling baik dibandingkan formula lain, basis lotion, maupun kontrol positif dengan aktivitas antibakteri sangat kuat, dilihat dari diameter zona hambat lebih dari 20 mm terhadap bakteri E. coli, S. aureus, and P. aeruginosa. Kata kunci: kelor (Moringa oleifera), aktivitas antibakteri, lotion